Multivariate fractional Taylor’s formula revisited - Anastassiou, George A. (Sarajevo Journal of Mathematics, 2024)
This is a continuation of [2]. Here is established a multivariate fractional Taylor's formula via the Caputo fractional derivative. The fractional remainder is expressed as a composition of two Riemann-Liouville fractional integrals. 2000 Mathematics Subject Classification. 26A33